Local Acidification Limits the Current Production and Biofilm Formation of Shewanella oneidensis MR-1 With Electrospun Anodes - Erben, Johannes; Pinder, Zachary A.; Lüdtke, Malte S.; Kerzenmacher, Sven (Frontiers in Microbiology, 2021)
The anodic current production of Shewanella oneidensis MR-1 is typically lower compared to other electroactive bacteria. The main reason for the low current densities is the poor biofilm growth on most anode materials. We demonstrate that the high current production of Shewanella oneidensis MR-1 with electrospun anodes exhibits a similar limiting current density as dense Geobacter spp. biofilms. This threshold current density is a result of local acidification in the biofilm. Increasing buffer concentration from 10 mM to 40 mM results in a 1.8-fold increase of the current density ((590 ± 25) µAcm−2) while biofilm growth stimulation by riboflavin has little effect on the current production. The current production of a reference material below the threshold did not respond to the increased buffer concentration but could be enhanced by supplemented riboflavin that stimulated the biofilm growth. Our results suggest that the current production with S. oneidensis is limited 1) by the biofilm growth on the anode that can be enhanced by the choice of the electrode material, and 2) by the proton transport through the biofilm and the associated local acidification.